Motivation and visit intention in the face of the insecurity situation due to drug trafficking. A tourist perception study in Mazatlán, Mexico - Hernández-Estrada, Diana Gisela (Universidad Autónoma de Tamaulipas, 2021)
The insecurity situation caused by organized crime represents a problem for tourism activity as it affects the decision to visit a destination. Particularly when the destination is close to areas with a history of illicit activities related to drug trafficking, as is the case of Mazatlán, Mexico. The objective of this study was to analyze tourist motivations regarding the intention to visit the city of Mazatlán, Sinaloa, in the face of insecurity due to drug trafficking. Through a quantitative research of explanatory scope, 453 domestic and foreign tourists were surveyed; and the obtained data were treated with partial least squares structural equation modeling (PLS-SEM) and other statistical techniques. The results show that, despite the situation of insecurity due to drug trafficking, pull motivations have a stronger impact than push motivations. However, both have a strong predictive capacity and relevance. On the other hand, the condition of insecurity due to drug trafficking influences the behavior of those surveyed and, therefore, they assume prevention and care behaviors in the spaces they visit. Likewise, foreigners perceive the ravages caused by organized crime to a lesser degree and have greater pull and push motivations; consequently, their intention to travel to this place is higher than that of Mexicans. It is concluded that in Mazatlán, regardless of the possibility of dangerous scenarios emanating from drug trafficking, there are stimuli that encourage vacationing. The contributions of this research can be of support in the development of marketing and security strategies for destinations, in order to attract more travelers.